RANCANG BANGUN FILTER PASIF UNTUK MEREDUKSI TOTAL HARMONIC DISTORTION (THD) AKIBAT PEMAKAIAN LAMPU HEMAT ENERGI (LHE) DAN LIGHT EMITTING DIODE (LED) - Alfronso Sinurat; Antonius Doddy Tyas Prasetyo; Eva Magdalena Silalahi; Bambang Widodo; Robinson Purba (Prodi Teknik Elektro FT UKI, 2021)
This paper discusses the design of a passive filter system for energy saving in Energy Saving Lamps (LHE) and Light Emitting Diode (LED), but for LHE and LED lamps for current Total Harmonic Distortion (THDi) that do not meet the standard. To reduce the current THD, it can be done by installing a single tune passive filter.””In this paper, we discuss the design of” a”passive filter system using a filter design with Matlab Simulink to determine the size of the components in filter design. To reduce the level of current harmonics, a single tune passive filter is designed which consists of an inductor and capacitor (LC) on the LHE and the LED.”Based on the research”data”that has been carried out,”the THDi measurement results for the lamp load test after using the filter are 49.12% for the LED circuit, 41.86% for the LHE circuit and 11.59% for the combined LED and LHE circuit.”Based on the results”of”each”measurement,”it can be seen that none have met the IEEE 519- 2014 standards. In this study, only using a filter tuned to the 3rd order, and based on the simulation results, it meets the IEEE 519-2014 standard, which is 1.11%.”The results of the design and testing of”tools (filters) show that they do not meet the IEEE 519-2014 standards, namely 11.59%.